Increasing ownership for intervention in ECOWAS. Issue 4 (1st October 2020) - Suzuki, Sanae
ABSTRACT: After the Cold War, not only the United Nations (UN) but also regional organisations began to engage in the internal conflicts of their member states. The Economic Community of West African States (ECOWAS) has long intervened in West African conflicts, and institutionalised its approach to interventions in 1999. Since then, member states have maintained and even increased their commitment to managing conflicts in West Africa regionally – a willingness that implies their ownership of interventions. This article argues that ECOWAS member states share ownership because they have developed a common understanding about intervention. The development of this common understanding is analysed with a focus on the origin and evolution of ECOWAS, that is, on the multi-level process of generating consensus and on the principle and practice of sharing the costs of resource mobilisation. I will show that, in practice, these processes led each state to perceive an enhanced sense of ownership in ECOWAS interventions. Case studies of ECOWAS interventions in Liberia, Sierra Leone, Guinea-Bissau and Cote d'Ivoire in the 1990s and the 2000s, the period when the organisation's interventions became institutionalised, support the argument.